Are small farms really more productive than large farms? - Fernando M. Aragon; Diego Restuccia; Juan Pablo Rud (Institute for Fiscal Studies (IFS), 2021)
This paper shows that using yields may not be informative of the relationship between farm size and productivity in the context of small-scale farming. This occurs because, in addition to productivity, yields pick up size-dependent market distortions and decreasing returns to scale. As a result, a positive relationship between farm productivity and land size may turn negative when using yields. We illustrate the empirical relevance of this issue with microdata from Uganda and show similar findings for Peru, Tanzania, and Bangladesh. In addition, we show that the dispersion in both measures of productivity across farms of similar size is so large that it renders farm size an ineffective indicator for policy targeting. Our findings stress the need to revisit the empirical evidence on the farm size-productivity relationship and its policy implications.
Keywords: O12; O13; Q12; Q15; 330; Farm size; productivity; yields; land markets; distortions; agriculture; policy